Striding towards sustainable urban livability: evaluating walkability efficiency vis-a-vis population dynamics in Saudi Arabia cities - Faisal Bin Sulaiman (Cogent Social Sciences, 2024)
AbstractThe pursuit of sustainable urban livability has become a paramount goal in contemporary urban planning, and walkability plays a pivotal role in creating pedestrian-friendly environments. This study investigates the walkability efficiency of selected Saudi Arabian cities, considering their unique population dynamics. Utilizing the Data Envelopment Analysis (DEA) method, we assess the efficiency of walkability factors across a diverse range of cities. The analysis encompasses a comprehensive set of input and output variables, including urban mobility aspects, street connectivity, safety measures, public spaces, and local urban governance. Our findings reveal that the majority of cities exhibit efficient walkability aligned with their population size and density (e.g. Makkah, Madinah, Jeddah, Riyadh, and Dammam). However, certain cities, namely Abha, Taif, Jazan, Hael, and Skaka, exhibited inefficiencies in their walkability. Additionally, we present graphical representations of efficient reference cities for inefficient ones, offering insights into potential pathways for improvement. This study contributes to the understanding of walkability efficiency in the Saudi Arabian context and highlights avenues for enhancing urban sustainability through strategic planning and development.